Separation membrane, its manufacturing method, filtration method and membrane filtration device
The separation membrane addresses the trade-off between water permeability and low fouling properties by utilizing a porous resin layer with specific polyvinylidene fluoride resin composition and structure, achieving excellent performance in both aspects along with high chemical resistance.
Patent Information
- Application Number
- JP2023559835
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-11-25
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-09-22
Smart Images

Figure 0007647921000004 
Figure 0007647921000001 
Figure 0007647921000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a separation membrane, a method for producing the same, a filtration method, and a membrane filtration device. [Background technology]
[0002] 2. Description of the Related Art In recent years, separation membranes such as microfiltration membranes and ultrafiltration membranes have been used in a variety of fields, including the water treatment field, such as water purification or wastewater treatment, the medical field, such as blood purification, and the food industry.
[0003] As mentioned above, the various separation membranes used in various ways may have a problem with operational stability if their permeability decreases due to deposition, adhesion, clogging, etc. (fouling) of the substances to be separated. In this case, it is necessary to increase the amount of aeration in the aeration cleaning or the frequency of chemical cleaning, which leads to increased operating costs, and therefore separation membranes with high permeability and low fouling are required. In addition, in water purification treatment, disinfectants such as sodium hypochlorite are added to the membrane module part, or the membrane itself is washed with acids, alkalis, chlorine, surfactants, etc., for the purpose of sterilizing the permeate water and preventing biofouling of the membrane. For this reason, separation membranes are required to have chemical durability (chemical resistance). Furthermore, in tap water production, accidents have become evident since the 1990s in which pathogenic microorganisms resistant to chlorine, such as Cryptosporidium derived from livestock manure, cannot be completely treated at the water purification plant and are mixed into the treated water. To prevent such accidents, separation membranes are required to have sufficient separation characteristics and high physical durability to prevent raw water from being mixed into the treated water.
[0004] In addition, treated water from separation membranes such as microfiltration membranes and ultrafiltration membranes may be treated with a reverse osmosis membrane or a nanofiltration membrane to be used as industrial water, drinking water, etc. In this case, the treated water from separation membranes such as microfiltration membranes and ultrafiltration membranes has a high concentration of biopolymers, and when used as treated water for a reverse osmosis membrane or a nanofiltration membrane, fouling due to adhesion of biopolymers may occur, which may impair the stability of operation.
[0005] As a separation membrane exhibiting excellent chemical resistance, a separation membrane containing a polymer containing a polyvinylidene fluoride resin is known. For example, Patent Document 1 discloses a technique for improving low fouling properties and separation properties by controlling the pore size distribution of a separation membrane made of a polymer containing a polyvinylidene fluoride resin. Patent Document 2 discloses a technique for increasing the pore size of the separation membrane and improving water permeability by selecting a long-chain branched fluoropolymer as the polyvinylidene fluoride resin contained in the separation membrane. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent No. 5310658 [Patent Document 2] Japan Special Publication No. 2016-510688 Summary of the Invention [Problem to be solved by the invention]
[0007] However, in conventional separation membranes made of polymers containing polyvinylidene fluoride resins, which aim to improve water permeability while also reducing fouling, it has been considered problematic that the two performances, which are in a trade-off relationship, cannot be fully achieved at the same time, and one of the two performances is sacrificed.In addition, there is a trade-off between separation ability and water permeability, and it has been considered problematic that one of the two performances is sacrificed. Therefore, an object of the present invention is to provide a separation membrane which has excellent low fouling properties, separation properties and water permeability, and also has high chemical resistance. [Means for solving the problem]
[0008] The present invention relates to the following (1) to (13). (1) A porous resin layer containing a polymer mainly composed of a polyvinylidene fluoride resin, In the porous resin layer, the number A of pores having a surface pore size of 0.01 μm or more and less than 0.05 μm and the number B of pores having a surface pore size of 0.05 μm or more satisfy a relationship of 2.0≦A / B≦15.0, The porous resin layer has a surface porosity of 10% or more, A separation membrane, wherein macrovoids having a short diameter of 10 μm or more are present in a region within 15 μm from the surface of the porous resin layer. (2) The separation membrane according to (1) above, wherein A and B satisfy the relationship A / B≧2.5. (3) The above B is 100 pieces / μm 2 The separation membrane according to (1) or (2), wherein the molecular weight is less than 1000. (4) The Lewis base component γ of the surface free energy of the porous resin layer m,- The value is 40mJ / m 2 The separation membrane according to any one of (1) to (3) above. (5) The Lewis base component γ of the surface free energy of the porous resin layer m,- The value is 45mJ / m 2 The separation membrane according to (4) above. (6) The separation membrane according to any one of (1) to (5), wherein the porosity occupied by the macrovoids in a region within 15 μm from the surface of the porous resin layer is 15% or more. (7) The separation membrane according to any one of (1) to (6), wherein in the porous resin layer, a surface pore ratio C of pores having a surface pore diameter of 0.01 μm or more and less than 0.05 μm and a surface pore ratio D of pores having a surface pore diameter of 0.05 μm or more satisfy a relationship of C / D≧0.6. (8) The separation membrane according to (7) above, wherein C and D satisfy a relationship of C / D≧0.8. (9) The separation membrane according to (8) above, wherein D is less than 8%. (10) The separation membrane according to any one of (1) to (9), comprising the porous resin layer and a support. (11) A method for filtering a liquid, using the separation membrane according to any one of (1) to (10). (12) A membrane filtration device using the separation membrane according to any one of (1) to (10) above. (13) A method for producing a separation membrane according to any one of (1) to (10), comprising the steps of: The method for producing a separation membrane includes: (i) a polymer solution preparation step of dissolving a polyvinylidene fluoride resin and a hydrophilic resin using a first non-solvent, a pore-opening agent, and a solvent to obtain a polymer solution; and (ii) a porous resin layer formation step of coagulating the polymer solution in a coagulation bath containing a second non-solvent to form a porous resin layer. Effect of the Invention
[0009] According to the present invention, it is possible to provide a separation membrane that has low fouling, excellent separation properties and water permeability while ensuring high chemical resistance due to the inclusion of a polymer mainly composed of a polyvinylidene fluoride resin. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is an enlarged image of a separation membrane illustrating the "three-dimensional mesh structure." DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings, but the present invention is not limited thereto. In this specification, the ratio (percentage, part, etc.) based on mass is the same as the ratio (percentage, part, etc.) based on weight.
[0012] (separation membrane) The separation membrane of the present invention is required to have a porous resin layer made of a polymer containing polyvinylidene fluoride resin as a main component (hereinafter, sometimes referred to as a "specific polymer").
[0013] The polyvinylidene fluoride resin refers to a vinylidene fluoride homopolymer or a vinylidene fluoride copolymer. Here, the vinylidene fluoride copolymer refers to a polymer having a vinylidene fluoride residue structure, and is typically a copolymer of a vinylidene fluoride monomer and other fluorine-based monomers. Examples of such fluorine-based monomers include vinyl fluoride, tetrafluoroethylene, hexafluoropropylene, and trifluorochloroethylene. The vinylidene fluoride copolymer may be copolymerized with ethylene or the like other than the above fluorine-based monomers to the extent that the effect of the present invention is not impaired.
[0014] The weight-average molecular weight of the polyvinylidene fluoride resin is preferably 50,000 to 1,000,000 because if it is too large, the water permeability of the separation membrane decreases, and if it is too small, the anti-fouling property of the separation membrane decreases. When the separation membrane is used for water treatment in which it is exposed to chemical cleaning, the weight-average molecular weight is preferably 100,000 or more, more preferably 150,000 or more. In addition, the weight-average molecular weight is preferably 900,000 or less, more preferably 800,000 or less. The weight average molecular weight of the polyvinylidene fluoride resin can be measured by gel permeation chromatography.
[0015] In the present invention, "containing polyvinylidene fluoride resin as a main component" means that the proportion of polyvinylidene fluoride resin in the polymer constituting the porous resin layer is 50% by mass or more. In order to ensure high chemical resistance, the proportion is preferably 55% by mass or more, and more preferably 60% by mass or more.
[0016] In order to achieve excellent low fouling and separation properties, the separation membrane of the present invention is required to have at least one surface layer made of a porous resin layer, and in the porous resin layer, the number of pores A having a surface pore size of 0.01 μm or more and less than 0.05 μm and the number of pores B having a surface pore size of 0.05 μm or more must satisfy the relationship A / B≧2.0. In other words, this means that on one surface of the porous resin layer, pores with large diameters and pores with small diameters are mixed at a certain ratio. The value of A / B is preferably 2.5 or more, more preferably 3.0 or more. The surface pore size here refers to the pore size on the surface that becomes the surface of the separation membrane.
[0017] On the other hand, in order for the separation membrane of the present invention to exhibit excellent water permeability, it is necessary that the relationship A / B≦15.0 is satisfied. The value of A / B is more preferably 12.0 or less, further preferably 10.0 or less, and most preferably 8.0 or less.
[0018] In order to increase the removal rate of biopolymers, the B is set to 100 particles / μm 2 It is preferable that the number of particles is less than 90 / μm. 2 It is more preferable that it is less than 1000 .mu.m.
[0019] In order to achieve excellent low fouling properties, the A is set to 200 particles / μm 2 More preferably, 300 particles / μm 2 More preferably, it is equal to or greater than this.
[0020] In order for the separation membrane of the present invention to exhibit excellent low fouling properties and water permeability, it is necessary that the surface porosity is 10% or more. With a high surface porosity, the target substance to be separated is dispersed in each pore, making fouling less likely to occur. The surface porosity is preferably 12% or more. In addition, the upper limit of the surface porosity is not particularly limited, but it is practical to set it to, for example, 30% or less.
[0021] The surface pore size and surface porosity of the porous resin layer are measured as follows. The surface of the porous resin layer is observed at a magnification of 10,000 times using a scanning electron microscope (hereinafter, SEM), and the diameter of each hole is calculated from the area of each hole when the hole is assumed to be a circle, and this is regarded as the hole diameter of each hole. The value obtained by dividing the sum of the areas of each hole by the area of the measured field of view can be regarded as the surface porosity.
[0022] In order to reduce the flow resistance when permeate flows through the porous resin layer and to exhibit high water permeability, the separation membrane of the present invention requires the presence of macrovoids in an area within 15 μm from the surface of the porous resin layer constituting the surface layer of the separation membrane. Here, the macrovoid in the present invention refers to a large void with a short diameter of 10 μm or more that exists in the porous resin layer, and hereinafter, when simply referred to as "macrovoid", this type of void is meant. The short diameter is the pore diameter measured in a direction parallel to the surface of the porous resin layer.
[0023] In the present invention, in order to achieve high water permeability, the porosity of the macrovoids in the region within 15 μm from the surface of the porous resin layer is preferably 15% or more, more preferably 25% or more. From the viewpoint of the strength of the porous resin layer, the porosity of the macrovoids in the region within 15 μm from the surface of the porous resin layer is preferably 80% or less, more preferably 50% or less. The porosity of the macrovoids in the region within 15 μm from the surface of the porous resin layer is, for example, 15 to 80%.
[0024] The separation membrane of the present invention has a Lewis base component γ of the surface free energy of the porous resin layer. m,- The value is 40mJ / m 2 More preferably, it is equal to or greater than this.
[0025] The separation membrane of the present invention is suitable for treating raw liquids such as natural water including river water, water containing a flocculant, activated sludge, fermented sludge, etc. All of these treated liquids contain a wide variety of components, and in the case of activated sludge and fermented sludge, they contain sugars and proteins, but there are also components that adhere to the membrane surface and block the pores as components that cause fouling of the separation membrane. Through extensive research, the present inventors have found a membrane that satisfies the above relationship, i.e., a membrane that has a Lewis base component γ of the surface free energy of the porous resin layer. m,- It was found that by increasing the adhesion force between the separation membrane and fouling components, the generation of fouling can be suppressed, and long-term stable operation can be achieved.
[0026] Lewis base component γ of the surface free energy of the porous resin layer m,- The value is 45 mJ / m 2 More preferably, it is equal to or greater than this.
[0027] The above γ m,- The value can be calculated based on the static contact angle between the porous resin layer surface and air in water, the static contact angle between the porous resin layer surface and air in ethylene glycol, and the static contact angle between the porous resin layer surface and diiodomethane in water, all of which are measured using a contact angle meter.
[0028] In order for the separation membrane of the present invention to exhibit excellent low fouling properties, the water contact angle of the surface of the porous resin layer is preferably 45° or less. In order to make the water contact angle of the surface of the porous resin layer 45° or less, a hydrophilic resin may be included in the polymer constituting the porous resin layer. The water contact angle of the surface of the porous resin layer is more preferably 40° or less.
[0029] Here, the term "hydrophilic resin" refers to a resin that has a high affinity for water and dissolves in water, or a resin that has a contact angle with water smaller than that of polyvinylidene fluoride resins. Examples of hydrophilic resins include cellulose esters such as cellulose acetate or cellulose acetate propionate, fatty acid vinyl esters, polyvinyl acetate, polyvinylpyrrolidone, ethylene oxide, propylene oxide, or polymethyl methacrylate, or polymers of acrylic acid esters or methacrylic acid esters, or copolymers of these polymers. The ratio of the hydrophilic resin to the total polymers constituting the porous resin layer is preferably 0.1 to 5% by mass.
[0030] In order to achieve excellent low fouling properties and separation properties, the separation membrane of the present invention has a surface porosity C of pores having a surface pore size of 0.01 μm or more and less than 0.05 μm in the porous resin layer and a surface porosity D of pores having a surface pore size of 0.05 μm or more, preferably C / D≧0.6, more preferably C / D≧0.8. In addition, in order to achieve excellent water permeability, the surface porosity C of pores having a surface pore size of 0.05 μm or more is preferably C / D≦5.0. The value of C / D is more preferably 4.0 or less, and even more preferably 3.0 or less. C / D satisfies, for example, the relationship 0.6≦C / D≦5.0.
[0031] In order to increase the removal rate of biopolymers, the above D is preferably less than 8%, and more preferably less than 7%.
[0032] In order to achieve excellent low fouling properties, the C content is preferably 4% or more, and more preferably 5% or more.
[0033] In the separation membrane of the present invention, in order to reduce the flow resistance when the permeate flows through the porous resin layer, it is preferable that macrovoids having a minor axis of 50 μm or more are present in the porous resin layer. On the other hand, from the viewpoint of the strength of the porous resin layer, it is preferable that the size of the macrovoids is limited to a minor axis of 300 μm or less. As described above, the minor axis is the pore diameter measured in a direction parallel to the surface of the porous resin layer.
[0034] In order to reduce the flow resistance when the permeate flows through the porous resin layer, the ratio of the short diameter of the macrovoids present in the porous resin layer to the average pore diameter of the surface of the porous resin layer is preferably 700 or more, and more preferably 1000 or more.
[0035] Here, the size of the macrovoids present in the porous resin layer can be determined by observing a cross section of the porous resin layer in a direction perpendicular to the surface thereof using an SEM.
[0036] The porosity occupied by macrovoids can be determined by using a confocal laser microscope to position a porous resin layer dyed with a fluorescent substance so that the axial direction of the laser light is perpendicular to the surface of the porous resin layer, and observing an area of 200 μm x 200 μm as a plane parallel to the surface, every 0.2 μm in an area up to 40 μm from the surface, and extracting a cross-sectional image perpendicular to the surface of the porous resin layer from the three-dimensional image created by stitching together the obtained images.
[0037] In the present invention, the porous resin layer preferably has a three-dimensional network structure in order to further enhance separation by homogenizing the polymer density of the surface layer due to entanglement of specific polymers with each other. Here, the "three-dimensional network structure" refers to a structure in which the polymers constituting the porous resin layer are spread three-dimensionally in a network shape as shown in Figure 1. The three-dimensional network structure has pores and voids partitioned by the polymers forming the network.
[0038] The separation membrane of the present invention preferably comprises the above-mentioned porous resin layer and other layers. The other layer is not particularly limited as long as it is a component capable of overlapping with the porous resin layer to form a layer. The other layer is preferably a support. Here, the "support" is a component that supports the porous resin layer and provides strength to the separation membrane. The material of the support is not particularly limited to organic materials, inorganic materials, etc., but organic fibers are preferred because they are easy to reduce in weight. The material is more preferably a woven or nonwoven fabric made of organic fibers such as cellulose fibers, cellulose triacetate fibers, polyester fibers, polypropylene fibers, and polyethylene fibers. Among them, the material is preferably a nonwoven fabric, which is relatively easy to control the density, easy to manufacture, and inexpensive.
[0039] If the thickness of the support is too thin, it becomes difficult to maintain the strength required for the separation membrane, and if it is too thick, the water permeability tends to decrease, so the thickness is preferably in the range of 50 μm to 1 mm, and most preferably in the range of 70 to 500 μm.
[0040] In the present invention, the thickness of the porous resin layer is preferably 50 μm or more, more preferably 80 μm or more, and even more preferably 100 μm or more. The thickness of the porous resin layer is preferably 500 μm or less, more preferably 300 μm or less, and even more preferably 200 μm or less. The thickness of the porous resin layer is, for example, 50 to 500 μm. If the porous resin layer is too thin, the support is exposed, and dirt components may adhere to the support, increasing the filtration pressure, or the filtration performance may not be fully restored even after washing. If the porous resin layer is too thick, the water permeability may decrease.
[0041] It is preferable that a part of the resin forming the porous resin layer penetrates at least the surface layer of the support and forms a composite layer with the support at least in the surface layer. By the resin penetrating into the support, the porous resin layer is firmly fixed to the support by a so-called anchor effect, and it becomes possible to prevent the porous resin layer from peeling off from the support.
[0042] The separation membrane of the present invention has a pure water permeability of 0.15 m at 25°C and 5 kPa, because it can reduce the operating pressure and inhibit the progression of fouling. 3 / m 2 / hr or more is preferable, and 0.5m 3 / m 2 / hr or more is more preferable.
[0043] (Membrane manufacturing method) The above-mentioned separation membrane of the present invention can typically be produced by the method described below.
[0044] The separation membrane of the present invention can be produced, for example, by a method including the following steps (i) and (ii). (i) A polymer solution preparation step of dissolving a polyvinylidene fluoride resin and a hydrophilic resin using a first non-solvent, a pore-opening agent, and a solvent to obtain a polymer solution. (ii) A porous resin layer forming step of coagulating the polymer solution in a coagulation bath containing a second non-solvent to form a porous resin layer.
[0045] In addition, in the separation membrane of the present invention, a manufacturing method in which the other layer is a support includes, for example, the above steps (i) and (ii), and in the (ii) porous resin layer formation step, a porous resin layer is formed on at least one surface of the support.
[0046] That is, first, a coating of a stock solution (polymer solution) containing a polyvinylidene fluoride resin, a hydrophilic resin, a first non-solvent, a pore-opening agent, and a solvent is formed on the surface of the support, and the stock solution is impregnated into the support. Then, the support is immersed in a coagulation bath containing a second non-solvent to coagulate the resin and form a porous resin layer on the surface of the support. From the viewpoint of film formation, it is usually preferable to select the temperature of the stock solution within the range of 15 to 120°C.
[0047] The density of the support is 0.7 g / cm 3 Preferably less than 0.6 g / cm3 If the density of the support is within this range, it is suitable for accepting the resin that forms the porous resin layer and forming an appropriate composite layer of the support and the resin. However, if the density is extremely low, the strength of the separation membrane tends to decrease, so the density of the support is set to 0.3 g / cm or less. 3 The density of the support is preferably 0.3 g / cm or more. 3 More than 0.7g / cm 3 The density referred to here is the apparent density, which can be calculated from the area, thickness and weight of the support.
[0048] The non-solvent is a liquid that does not dissolve the resin. The first non-solvent in the above step (i) acts to control the speed of resin solidification and thereby control the size of the pores. As the first non-solvent in the above step (i), water or alcohols such as methanol and ethanol can be used. When a hydrophilic resin is used, it is preferable to use a polyhydric alcohol in order to achieve a surface porosity of 10% or more and to exhibit excellent water permeability. In particular, the Lewis base component γ of the surface free energy of the porous resin layer m,- value of 40mJ / m 2 In order to achieve the above-mentioned ratio A / B of 2.0 or more and to exhibit excellent low fouling properties and separation properties, it is preferable that glycerin is contained.
[0049] The pore-opening agent is extracted when immersed in a coagulation bath and has the effect of making the resin layer porous. The pore-opening agent is preferably one that is highly soluble in the coagulation bath. For example, inorganic salts such as calcium chloride and calcium carbonate can be used. Polyoxyalkylenes such as polyethylene glycol (PEG) and polypropylene glycol, surfactants, etc. can also be used. The pore-opening agent can be selected arbitrarily, but a polymer mainly composed of PEG or a surfactant is preferable. Among them, it is particularly preferable to use a polymer mainly composed of PEG having a weight average molecular weight of 10,000 or more and 50,000 or less, or a surfactant having a polyoxyalkylene structure, a fatty acid ester structure, and a hydroxyl group as the pore-opening agent. By using these as the pore-opening agents, the porosity of the macrovoids in the region within 15 μm from the surface of the porous resin layer is likely to be 15% or more. Here, "mainly composed" means that the pore-opening agent contains the component in question at 50% by weight or more.
[0050] Examples of surfactants having a polyoxyalkylene structure, a fatty acid ester structure, and a hydroxyl group include polyethylene glycol monooleate, polyethylene glycol monostearate, polyoxyethylene sorbitan monolaurate (Tween 20), polyoxyethylene sorbitan monostearate (Tween 60), and polyoxyethylene sorbitan monooleate (Tween 80).
[0051] The solvent dissolves the resin. The solvent acts on the resin and the pore-opening agent to promote their formation of a porous resin layer. As the solvent, NMP, N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), dimethylsulfoxide (DMSO), acetone, methyl ethyl ketone, etc. can be used. Among them, NMP, DMAc, DMF, and DMSO, which have high resin solubility, can be preferably used.
[0052] The second non-solvent in the above step (ii) acts to control the speed of resin solidification and to control the size of pores and macrovoids. As the second non-solvent, water or alcohols such as methanol and ethanol can be used. Among them, the second non-solvent is preferably water in terms of ease of wastewater treatment and cost. The second non-solvent may be a mixture containing these.
[0053] In the polymer solution preparation step, it is preferable to use a polyvinylidene fluoride resin, a hydrophilic resin, a first non-solvent, a pore-opening agent, and a solvent to obtain a polymer solution (stock solution) in which the polyvinylidene fluoride resin and the hydrophilic resin are dissolved. In the stock solution, it is preferable that the polyvinylidene fluoride resin is 5 to 30% by weight, the hydrophilic resin is 0.1 to 5% by weight, the pore-opening agent is 0.1 to 15% by weight, the solvent is 40 to 94.4% by weight, and the first non-solvent is 0.5 to 20% by weight. If the polyvinylidene fluoride resin is extremely small, the strength of the separation membrane (porous resin layer) may be reduced, and if it is too much, the water permeability may be reduced. The content of the polyvinylidene fluoride resin in the stock solution is more preferably within the range of 8 to 20% by weight. If the hydrophilic resin is too small, the water contact angle of the surface of the porous resin layer may increase, and if it is too much, the surface porosity may be reduced. The content of the hydrophilic resin in the stock solution is more preferably in the range of 0.2 to 2% by weight. If the amount of the pore-opening agent is too small, the water permeability may decrease, and if the amount is too large, the strength of the separation membrane (porous resin layer) may decrease. If the amount is too large, the pore-opening agent may remain in the porous resin layer and dissolve during use, causing the quality of the permeate to deteriorate and the water permeability to fluctuate. The content of the pore-opening agent in the stock solution is more preferably in the range of 0.5 to 10% by weight. If the amount of the solvent is too small, the stock solution may easily gel, and if the amount is too large, the strength of the separation membrane (porous resin layer) may decrease. The content of the solvent in the stock solution is more preferably in the range of 60 to 90% by weight. If the proportion of the first non-solvent in the stock solution is too high, the stock solution may easily gel, so the first non-solvent in the stock solution is preferably in the range of 0.5 to 20% by weight. More preferably, it is in the range of 0.5 to 15% by weight.
[0054] In the porous resin layer forming step, it is preferable to form the porous resin layer by coagulating the above-mentioned polymer solution (raw solution) in a coagulation bath containing a second non-solvent. The coagulation bath can be a second non-solvent or a mixed solution containing the second non-solvent and a solvent. In the coagulation bath, the second non-solvent is preferably at least 80% by weight. If the amount is too small, the coagulation speed of the resin slows down, the pore size of the surface becomes large, and macrovoids are difficult to generate. More preferably, it is in the range of 85 to 100% by weight. Note that if the temperature of the coagulation bath is too high, the coagulation speed becomes too fast, and conversely, if it is too low, the coagulation speed becomes too slow, so it is usually preferable to select the temperature within the range of 15 to 80°C. A more preferable temperature range is 20 to 60°C.
[0055] When forming a separation membrane in which the other layer is a support, it is preferable to form a porous resin layer on at least one surface of the support in the porous resin layer forming step. The film of the stock solution on the support can be formed by applying the stock solution to the support or by immersing the support in the stock solution. When applying the stock solution, it may be applied to one side or both sides of the support. In this case, depending on the composition of the stock solution, it is preferable to apply a porous resin layer on at least one surface of the support. 3 It is preferable to use a support having a temperature not higher than 100° C., since this allows the support to be appropriately impregnated with the stock solution.
[0056] After the porous resin layer forming step, it is preferable to provide a washing step for removing the solvent and the pore-opening agent. The washing method can be appropriately selected depending on the type of the solvent and the pore-opening agent, and is not particularly limited, but an example of the washing method is immersion in hot water at 60 to 100°C for 1 to 10 minutes.
[0057] The shape of the produced separation membrane can be controlled by the state of coagulation of the polymer solution in the porous resin layer forming step. When producing a flat separation membrane, for example, a film-like support made of a nonwoven fabric, a metal oxide, a metal, or the like, coated with the polymer solution can be immersed in a coagulation bath.
[0058] When producing a hollow fiber separation membrane, the polymer solution can be discharged from the outer periphery of the double tube nozzle and the core liquid can be discharged from the center into a coagulation bath containing a second non-solvent at the same time. As the core liquid, it is preferable to use a good solvent in the polymer solution preparation process. A separation membrane may be formed on the surface of a hollow fiber support made of a polymer, metal oxide, metal, or the like. Examples of a method for forming a separation membrane on the surface of a hollow fiber support made of a polymer include a method of simultaneously discharging a solution that is a raw material for the hollow fiber support and a polymer solution using a triple tube nozzle, or a method of passing a polymer solution applied to the outer surface of a hollow fiber support previously formed into a membrane through a second non-solvent in a coagulation bath.
[0059] The separation membrane of the present invention can be applied to both ultrafiltration membranes and microfiltration membranes. The water to be treated by the separation membrane of the present invention is not particularly limited, but is preferably used in the separation of activated sludge for biological treatment of sewage or wastewater containing suspended solids of relatively large particles.
[0060] The treated water from the separation membrane of the present invention is preferably used as the treated water for a reverse osmosis membrane or a nanofiltration membrane. Since the separation membrane of the present invention has high separation ability, the treated water from the separation membrane of the present invention has a low biopolymer concentration, and when used as the treated water for a reverse osmosis membrane or a nanofiltration membrane, fouling due to adhesion of biopolymers can be suppressed.
[0061] The membrane filtration device using the separation membrane of the present invention obtained as described above can be used to filter liquids. As an example of the membrane filtration device, a plurality of elements, each having a separation membrane attached via a plastic net to both sides of a support frame having a filtrate outlet at the top, are arranged in parallel, and housed in a water tank to be treated having an aeration device at the bottom, and equipped with a blower and a suction pump, are considered, but are not limited to these.
[0062] As a method for filtering a liquid, for example, the above-mentioned membrane filtration device can be used to remove suspended matter contained in raw liquid such as activated sludge used for biological treatment of sewage or wastewater, which contains relatively large suspended matter particles, but is not limited to this. EXAMPLES
[0063] The present invention will be specifically described below by way of examples, but the present invention is not limited to these in any way.
[0064] (i) Surface pore size, number of pores and surface porosity of porous resin layer The surface of the porous resin layer in the separation membrane was observed under the following observation conditions using an SEM (Hitachi High-Technologies Corporation; S-5500), and the area of each hole in the observation field was measured. From the area of each hole, the diameter when the hole was assumed to be a circle was calculated as the hole diameter. The sum of the areas of each hole was divided by the area of the observation field to calculate the surface porosity. The number of holes with a pore diameter of 0.01 μm or more and less than 0.05 μm was divided by the area of the observation field to calculate the number A of holes with a pore diameter of 0.01 μm or more and less than 0.05 μm per unit area, and the number of holes with a pore diameter of 0.05 μm or more was divided by the area of the observation field to calculate the number B of holes with a pore diameter of 0.05 μm or more per unit area. In addition, the area occupied by pores with a pore size of 0.01 μm or more and less than 0.05 μm was divided by the area of the observation field to calculate the surface porosity C of pores with a pore size of 0.01 μm or more and less than 0.05 μm, and the area occupied by pores with a pore size of 0.05 μm or more was divided by the area of the observation field to calculate the surface porosity D of pores with a pore size of 0.05 μm or more. Acceleration voltage: 5kV Observation magnification: 30,000 times Observation field of view: 4.233μm×3.175μm Image processing software: ImageJ (Wayne Rasband, National Institutes of Health) The measurements were performed on 10 random visual fields, and the number of holes A and the number of holes B, the surface porosity C and the surface porosity D were calculated for each visual field. The average values were taken as the number of holes A and the number of holes B, the surface porosity C and the surface porosity D.
[0065] (ii) Water contact angle The separation membrane was cut into 3 cm squares, immersed overnight in a 25% by mass aqueous solution of ethanol, and then immersed in water for more than 2 hours to prepare a sample. The sample was fixed to a three-state sample stand (manufactured by Kyowa Interface Science Co., Ltd.) with a three-state magnet (manufactured by Kyowa Interface Science Co., Ltd.) so that the surface of the porous resin layer was facing down, and placed in a three-state cell (manufactured by Kyowa Interface Science Co., Ltd.) containing distilled water, and air bubbles were generated on the surface of the porous resin layer. The static contact angle was measured in an atmosphere of 25°C using a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd.; DropMaster DM500), and the value obtained by subtracting this value from 180° was determined as the water contact angle.
[0066] (iii) Lewis base component of the surface free energy of the porous resin layer The separation membrane was cut into 3 cm squares, immersed overnight in a 25% by mass aqueous ethanol solution, and then immersed in water for more than 2 hours to prepare a sample. The sample was fixed to a three-state sample stand (manufactured by Kyowa Interface Science Co., Ltd.) with a three-state magnet (manufactured by Kyowa Interface Science Co., Ltd.) so that the surface of the porous resin layer was facing down, and placed in a three-state cell (manufactured by Kyowa Interface Science Co., Ltd.) containing distilled water or ethylene glycol, bubbles were generated on the surface of the porous resin layer, and the static contact angle was measured in an atmosphere of 25 ° C. using a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd.; DropMaster DM500). The sample was also fixed to a three-state sample stand with a three-state magnet so that the surface of the porous resin layer was facing up, and placed in a three-state cell containing distilled water, diiodomethane was dropped on the surface of the porous resin layer, and the static contact angle was measured in an atmosphere of 25 ° C. using a contact angle meter. From the contact angles thus obtained, the static contact angles θ1 of water, ethylene glycol, and diiodomethane on the surface of the porous resin layer were calculated, and these were substituted into the following equation 1, respectively, to obtain a simultaneous equation consisting of the four equations: γ LW , γ + , γ - The Lewis base component γ of the surface free energy of the porous resin layer is calculated by solving the above equation. - asked for. (γ m,LW Gamma l,LW ) 1 / 2 +(γ m,+ Gamma l,- ) 1 / 2 +(γm,- Gamma l,+ ) 1 / 2 =(1+cosθ1)[γ l,LW +2(γ l,+ Gamma l,- ) 1 / 2 ] / 2 ···(Formula 1)
[0067] Here, γ m,LW , γ m,+ , γ m,- represent the van der Waals component, Lewis acid component, and Lewis base component of the surface free energy of the porous resin layer, respectively, and γ l,LW , γ l,+ , γ l,- represent the van der Waals component, Lewis acid component, and Lewis base component of the surface free energy of each liquid, respectively. The surface free energy of each liquid used here is the value in Table 1 proposed by Oss ("Fundamentals of Adhesion", LH Lee (Ed.), p. 153, Plenum ess, New York (1991)).
[0068] (iv) Minor diameter of macrovoids in the porous resin layer A cross-sectional measurement sample was prepared from the separation membrane by the frozen ultrathin section method, and the minor axis of the macrovoid was calculated from the size of the macrovoid observed under the following observation conditions using a SEM (Hitachi High-Technologies Corporation; S-5500). Acceleration voltage: 5kV Observation magnification: 500x Observation area: 256μm×192μm The measurement was carried out for 10 random visual fields, the minor diameters of the macrovoids observed were measured, and the average value was regarded as the minor diameter of the macrovoids in the porous resin layer.
[0069] (v) The porosity of macrovoids in the region within 15 μm from the surface of the porous resin layer The separation membrane was stained with a fluorescent substance (3,3,3',3'-tetramethyl-1,1'-bis(4-sulfobutyl)indocarbocyanine sodium), and a confocal laser microscope (Olympus Corporation; FV3000) was used to set the porous resin layer surface and the axial direction of the laser light perpendicular to each other, and a 200 μm x 200 μm area was observed as a plane parallel to the surface, and an area up to 40 μm from the surface was observed every 0.2 μm. From the three-dimensional image obtained by stitching together the images, a cross-sectional image perpendicular to the surface of the porous resin layer was extracted, and the area S1 up to 15 μm from the surface was calculated. The observed cross-sectional image was binarized with the structure and pores made of resin, and the area S2 of the macrovoids occupying within 15 μm from the surface of the porous resin layer was calculated. The porosity (%) was calculated from the following formula 2. (Porosity)=S2 / S1×100 (Formula 2) Any five images were measured, and the average value was taken as the porosity.
[0070] (vi) Pure water permeability of separation membrane The separation membrane was cut into a circle with a diameter of 50 mm and set in a cylindrical filtration holder (Ultra Holder UHP-43K, manufactured by Advantec Toyo Co., Ltd.). Distilled water was pre-permeated at 25°C and a pressure of 5 kPa for 5 minutes, and then the permeated water was sampled for 3 minutes. The unit time (h) and unit membrane area (m 2 ) and calculated.
[0071] (vii) Blockage and filtration resistance of separation membrane The separation membrane was cut into a circle with a diameter of 50 mm, soaked in ethanol overnight, and then soaked in water for at least 2 hours, and set in a cylindrical filter holder (Ultra Holder UHP-43K, manufactured by Advantec Toyo Co., Ltd.). Activated sludge (50 g) with a concentration of 7,000 mg / L was placed in the filter holder, the stirring speed was adjusted to 450 rpm, and the membrane permeation flux, converted to the amount of water permeated (cubic meters) per day per square meter of membrane surface at an evaluation temperature of 25°C, was 3.0 m 3 / m 2 / day, filter for 2 minutes, and calculate the sludge filtration resistance from the amount of permeated water during the first 5 seconds of filtration. Axx represents the number of times that the 2-minute filtration of the activated sludge was repeated, and in the first filtration, x = 1. Here, the filtration resistance was calculated from the following formula 5. Res=P×t×S / (μ×L) (Formula 5) Res: Filtration resistance P: Evaluation pressure t: Filtration time S: Membrane area μ: Viscosity L: Filtration volume
[0072] After the filtration was stopped, the stirring speed was increased to 450 rpm for 1 minute. With the separation membrane still set in the filter holder, the remaining activated sludge solution in the filter holder was removed, the filter holder was filled with distilled water, and the stirring speed was increased to 450 rpm for 1 minute.
[0073] Activated sludge filtration and membrane cleaning were repeated for 2 minutes, and the Res A1 ~Res A5 Res was measured. An+1 -Res An was calculated for values of n from 1 to 4, and the average value was taken as the degree of increase in clogging filtration resistance. Note that the smaller the value of the degree of increase in clogging filtration resistance, the more excellent the separation membrane's anti-fouling properties can be evaluated. In Tables 2 and 3, the degree of increase in clogging filtration resistance is shown as "clogging filtration resistance."
[0074] (viii) Biopolymer Removal Ability of the Separation Membrane The separation membrane was cut into a circle with a diameter of 50 mm, immersed in a 25% by mass aqueous ethanol solution overnight, then immersed in water for more than 2 hours, and set in a cylindrical filter holder (Ultra Holder UHP-43K, manufactured by Advantec Toyo Co., Ltd.). Activated sludge (50 g) with a concentration of 7,000 mg / L was placed in the filter holder, the stirring speed was adjusted to 450 rpm, and 20 g was filtered at an evaluation temperature of 25°C and an evaluation pressure of 5 kPa. The biopolymer concentration in the activated sludge and filtrate was measured using size exclusion liquid chromatography (LC-OCD Model 8, manufactured by DOC-Labor Co., Ltd.), and the biopolymer removal rate was calculated from the following formula 6. Rej=100×(1-CP / CF) (Formula 6) Rej: Biopolymer removal rate CF: Biopolymer concentration in raw water CP: Biopolymer concentration in the filtrate
[0075] (ix) Method for producing reverse osmosis membrane Polyester nonwoven fabric (breathability 0.5~1cc / cm 2 A 15.7 wt% DMF solution of polysulfone was cast on a substrate at room temperature (25°C) with a thickness of 200 μm, and immediately immersed in pure water and left for 5 minutes to prepare a microporous support membrane (thickness 210-215 μm). The obtained microporous support membrane was cut into a 20 cm square, fixed to a metal frame, and immersed in a 1.8 wt% aqueous solution of m-phenylenediamine as a polyfunctional amine aqueous solution for 2 minutes. The support membrane was slowly pulled up vertically from the aqueous solution, and nitrogen was sprayed from an air nozzle to remove excess aqueous solution from the support membrane surface. Then, 25 ml of a 25°C n-decane solution containing 0.065 wt% trimesic acid chloride was poured into the frame so that the surface of the support membrane was completely wet, and the n-decane solution was left to stand for 1 minute from the initial contact of the support membrane with the support membrane. Next, the membrane was held vertically for 1 minute to remove excess solution from the membrane, and then washed with 80°C hot water for 2 minutes. Further, the washed membrane was immersed in a 0.3 wt % aqueous sodium nitrite solution of pH 3 at 35° C. for 1 minute, and then in a 0.1 wt % aqueous sodium sulfite solution for 2 minutes to obtain a reverse osmosis membrane.
[0076] (x) Water retention rate of reverse osmosis membrane The separation membrane was cut into a circle with a diameter of 50 mm, immersed in a 25% by mass aqueous ethanol solution overnight, and then immersed in water for more than 2 hours, and set in a cylindrical filter holder (Ultra Holder UHP-43K, manufactured by Advantec Toyo Co., Ltd.). Activated sludge (50 g) with a concentration of 7,000 mg / L was placed in the filter holder, the stirring speed was adjusted to 450 rpm, and 25 g was filtered at an evaluation temperature of 25°C and an evaluation pressure of 5 kPa. This operation was performed twice to obtain a total of 50 g of filtered water. The reverse osmosis membrane obtained in (viii) above was cut into a circle with a diameter of 50 mm, soaked in pure water overnight, and then set in a cylindrical filtration holder (Ultra Holder UHP-43K, manufactured by Advantec Toyo Co., Ltd.). The filtrate (50 g) of the separation membrane was placed in the filtration holder, and 5 g was filtered at an evaluation temperature of 25° C. and an evaluation pressure of 0.4 MPa. The amount of permeated water L1 for the first minute during filtration and the amount of permeated water L2 for the last 5 minutes during filtration were measured, and the water permeation retention rate L2 / (5×L1) was calculated.
[0077] Example 1 Polyvinylidene fluoride (hereinafter referred to as "PVDF") (weight average molecular weight 600,000) and cellulose acetate (hereinafter referred to as "CA") were added with DMF as a solvent, PEG (weight average molecular weight 20,000) as a pore-opening agent, and glycerin as a first non-solvent, and thoroughly stirred at a temperature of 100°C to prepare a polymer solution with the following composition ratio. PVDF: 11% by weight CA: 0.4% by weight DMF: 73% by weight PEG: 9% by weight Glycerin: 6.6% by weight
[0078] Next, density 0.6g / cm 3 The prepared polymer solution was applied to the surface of a polyester fiber nonwoven fabric as a support. After application, the fabric was immediately immersed in pure water at 20°C for 5 minutes to form a porous resin layer. It was then immersed in hot water at 90°C for 2 minutes to wash out the DMF solvent and the PEG pore-opening agent, forming a separation membrane with a three-dimensional network structure in the porous resin layer.
[0079] The evaluation results of the obtained separation membrane are shown in Table 2. The number A of pores having a surface pore size of 0.01 μm or more and less than 0.05 μm in the porous resin layer was 299 pores / μm 2 The number of pores B with a surface pore size of 0.05 μm or more is 81 / μm 2 , A / B value is 3.7, surface porosity is 12.6%, water contact angle is 39.2°, γ m,- The value is 50mJ / m 2The surface porosity C of pores in the porous resin layer with a surface pore diameter of 0.01 μm or more and less than 0.05 μm was 5.8%, the surface porosity D of pores with a surface pore diameter of 0.05 μm or more was 6.7%, the C / D value was 0.9, and the porosity occupied by macrovoids in the region within 15 μm from the surface of the porous resin layer was 37.3%. The pure water permeability, which is an indicator of permeability performance, the increase in clogging filtration resistance, which is an indicator of low-fouling performance, and the biopolymer removal rate, which is an indicator of removal performance, all showed excellent values.
[0080] Example 2 A separation membrane having a porous resin layer with a three-dimensional network structure was formed in the same manner as in Example 1, except that the composition of the polymer solution was as shown below. PVDF: 12% by weight CA: 0.4% by weight DMF: 72% by weight PEG: 9% by weight Glycerin: 6.6% by weight
[0081] The evaluation results of the obtained separation membrane are shown in Table 2. The value of A was 333 particles / μm 2 , B is 74 pieces / μm 2 , A / B value is 4.5, surface porosity is 12.2%, water contact angle is 42.6°, γ m,- The value is 53 mJ / m 2 The C value was 6.4%, the D value was 5.8%, the C / D value was 1.1, and the porosity occupied by macrovoids in the region within 15 μm from the surface of the porous resin layer was 24.9%. The pure water permeability, increase in clogging filtration resistance, and biopolymer removal rate all showed excellent values.
[0082] Example 3 A separation membrane having a porous resin layer with a three-dimensional network structure was formed in the same manner as in Example 1, except that the composition of the polymer solution was as follows: Here, EG stands for ethylene glycol. PVDF: 11% by weight CA: 0.4% by weight DMF: 70% by weight PEG: 9% by weight Glycerin: 6.6% by weight EG: 3% by weight
[0083] The evaluation results of the obtained separation membrane are shown in Table 2. The value of A was 363 particles / μm 2 , B is 85 pieces / μm 2 , A / B value is 4.3, surface porosity is 13.1%, water contact angle is 42.5°, γ m,- The value is 58 mJ / m 2 The C value was 7.3%, the D value was 6.6%, the C / D value was 1.1, and the porosity occupied by macrovoids in the region within 15 μm from the surface of the porous resin layer was 32.8%. The pure water permeability, increase in clogging filtration resistance, and biopolymer removal rate all showed excellent values.
[0084] Example 4 A separation membrane having a porous resin layer with a three-dimensional network structure was formed in the same manner as in Example 1, except that the composition of the polymer solution was as shown below. PVDF: 12% by weight CA: 0.4% by weight DMF: 69% by weight PEG: 9% by weight Glycerin: 6.6% by weight EG: 3% by weight
[0085] The evaluation results of the obtained separation membrane are shown in Table 2. The value of A was 384 particles / μm 2 , B is 57 / μm 2 , A / B value is 6.7, surface porosity is 10.4%, water contact angle is 40.8°, γ m,- The value is 56 mJ / m 2 The C value was 6.5%, the D value was 3.9%, the C / D value was 1.7, and the porosity occupied by macrovoids in the region within 15 μm from the surface of the porous resin layer was 27.5%. The pure water permeability, increase in clogging filtration resistance, and biopolymer removal rate all showed excellent values.
[0086] Comparative Example 1 A separation membrane having a porous resin layer with a three-dimensional network structure was formed in the same manner as in Example 1, except that the composition of the polymer solution was as shown below. PVDF: 11% by weight DMF: 73.4% by weight PEG: 9% by weight Glycerin: 6.6% by weight
[0087] The evaluation results of the obtained separation membrane are shown in Table 3. The value of A was 111 particles / μm 2 , B is 97 / μm 2 , A / B value is 1.1, surface porosity is 14.9%, water contact angle is 53.5°, γ m,- The value is 27 mJ / m 2 The C value was 2.4%, the D value was 12.4%, the C / D value was 0.2, and the porosity occupied by macrovoids in the region within 15 μm from the surface of the porous resin layer was 29.1%, and the biopolymer removal rate was inferior to the results of the examples.
[0088] Comparative Example 2 A separation membrane having a porous resin layer with a three-dimensional network structure was formed in the same manner as in Example 1, except that the composition of the polymer solution was as shown below. PVDF: 11% by weight CA: 0.4% by weight DMF: 79.6% by weight PEG: 9% by weight
[0089] The evaluation results of the obtained separation membrane are shown in Table 3. The value of A was 59 particles / μm 2 , B is 81 pieces / μm 2 , A / B value is 0.7, surface porosity is 15.7%, water contact angle is 42.4°, γ m,- The value is 56 mJ / m 2 The C value was 1.3%, the D value was 14.4%, the C / D value was 0.1, and the porosity occupied by macrovoids in the region within 15 μm from the surface of the porous resin layer was 17.8%, and the biopolymer removal rate was inferior to the results of the examples.
[0090] Comparative Example 3 A separation membrane having a porous resin layer with a three-dimensional network structure was formed in the same manner as in Example 1, except that the composition of the polymer solution was as shown below. PVDF: 11% by weight DMF: 73.4% by weight PEG: 9% by weight H2O: 6.6% by weight
[0091] The results of evaluation of the obtained separation membrane are shown in Table 3. The value of A is 40 particles / μm 2 , B is 67 / μm 2 , A / B value is 0.6, surface porosity is 14.3%, water contact angle is 50.7°, γ m,- The value is 32 mJ / m 2 The C value was 0.9%, the D value was 13.4%, the C / D value was 0.1, and the porosity occupied by macrovoids in the region within 15 μm from the surface of the porous resin layer was 17.4%. The increase in clogging filtration resistance and the biopolymer removal rate were inferior to the results of the examples.
[0092] Comparative Example 4 A separation membrane having a porous resin layer with a three-dimensional network structure was formed in the same manner as in Example 1, except that the composition of the polymer solution was as shown below. PVDF: 11% by weight CA: 0.4% by weight DMF: 82% by weight H2O: 6.6% by weight
[0093] The evaluation results of the obtained separation membrane are shown in Table 3. The value of A was 122 particles / μm 2 , B is 54 pieces / μm 2 , A / B value is 2.3, surface porosity is 7.9%, water contact angle is 43.7°, γ m,- The value is 46 mJ / m 2 The C value was 2.9%, the D value was 5.0%, the C / D value was 0.6, and the porosity occupied by macrovoids in the region within 15 μm from the surface of the porous resin layer was 21.2%, and the degree of increase in clogging filtration resistance was inferior compared to the results of the examples.
[0094] (Water retention rate of reverse osmosis membrane) Using the filtrates from the separation membranes described in Example 1 and Comparative Example 1, the water permeability retention of the reverse osmosis membrane was evaluated.
[0095] When the filtrate from the separation membrane of Example 1 was used, the water permeability retention rate of the reverse osmosis membrane was 0.60, and when the filtrate from the separation membrane of Comparative Example 1 was used, the water permeability retention rate of the reverse osmosis membrane was 0.31. The water permeability retention rate of the reverse osmosis membrane was superior when the filtrate from the separation membrane of Example 1 was used.
[0096] [Table 1]
[0097] [Table 2]
[0098] [Table 3]
[0099] Although the present invention has been described in detail with reference to specific embodiments, it will be apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the invention. This application is based on a Japanese patent application (Patent Application No. 2022-157515) filed on September 30, 2022 and a Japanese patent application (Patent Application No. 2022-188062) filed on November 25, 2022, the entire contents of which are incorporated by reference. [Industrial Applicability]
[0100] The separation membrane according to the present invention has excellent low fouling properties, separation properties and water permeability while ensuring high chemical resistance, and is therefore suitable for use in various fields, such as the water treatment field, e.g., water purification or wastewater treatment, the medical field, e.g., blood purification, and the food industry.
Claims
1. A porous resin layer containing a polymer mainly composed of a polyvinylidene fluoride resin is provided. In the porous resin layer, the number A of pores having a surface pore diameter of 0.01 μm or more and less than 0.05 μm and the number B of pores having a surface pore diameter of 0.05 μm or more satisfy a relationship of 2.0≦A / B≦15.0, The A is 200 particles / μm 2 or more, The porous resin layer has a surface porosity of 10% or more, A separation membrane, wherein macrovoids having a short diameter of 10 μm or more are present in a region within 15 μm from the surface of the porous resin layer.
2. The separation membrane according to claim 1 , wherein the relationship between A and B is A / B≧2.
5.
3. The above B is 100 pieces / μm 2 The separation membrane according to claim 1 , wherein the molecular weight is less than 1000.
4. The Lewis base component γ of the surface free energy of the porous resin layer m,- The value is 40 mJ / m 2 The separation membrane according to claim 1 .
5. The Lewis base component γ of the surface free energy of the porous resin layer m,- The value is 45 mJ / m 2 The separation membrane according to claim 4 .
6. 2. The separation membrane according to claim 1, wherein the porosity occupied by the macrovoids in a region within 15 μm from the surface of the porous resin layer is 15% or more.
7. 2. The separation membrane according to claim 1, wherein in the porous resin layer, a surface porosity C of pores having a surface pore diameter of 0.01 μm or more and less than 0.05 μm and a surface porosity D of pores having a surface pore diameter of 0.05 μm or more satisfy a relationship of C / D≧0.
6.
8. The separation membrane according to claim 7 , wherein the relationship between C and D is C / D≧0.
8.
9. The separation membrane according to claim 8 , wherein D is less than 8%.
10. The separation membrane according to claim 1 , comprising the porous resin layer and a support.
11. A method for filtering a liquid using the separation membrane according to any one of claims 1 to 10.
12. A membrane filtration device using the separation membrane according to any one of claims 1 to 10.
13. A method for producing a separation membrane according to any one of claims 1 to 10, The method for producing a separation membrane includes: (i) a polymer solution preparation step of dissolving a polyvinylidene fluoride resin, a hydrophilic resin, a first non-solvent, a pore-opening agent, and a solvent to obtain a polymer solution; and (ii) a porous resin layer formation step of coagulating the polymer solution in a coagulation bath containing a second non-solvent to form a porous resin layer.
Citation Information
Patent Citations
Method of producing tubular film and annular die for extrusion molding same
JP1978010658A
Asymmetrical porous membrane of polyvinyl fluoride and its production
JP1983091731A
Porous membrane
JP2004202438A
Hollow fiber membrane, hollow fiber membrane module using it, membrane filtering device and water treating method
JP2006231274A
Porous separation flat membrane and method of manufacturing the same
JP2011189266A